2009
DOI: 10.1021/jo901753z
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Domino Reactions:N-(Adamantyl)phthalimides andN-(Adamantylalkyl)phthalimides

Abstract: Phthalimides 1-6 undergo photochemical reactions upon direct irradiation as well as triplet sensitization and give rise to new products. Besides formation of the primary photoproducts, the first photochemical step initiates a subsequent thermal domino reaction or a domino sequence of a thermal and a photochemical reaction. The latter, involving two photochemical intramolecular gamma-H abstractions, was observed with phthalimides 1, 3, and 6 and delivered stereospecifically the hexacyclic benzazepine products 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 104 publications
1
22
0
Order By: Relevance
“…Using F 4 -stilbene 1, we performed a photoinduced domino reaction consisting of three photochemical steps: oxidative photocyclisation/photoinduced Diels-Alder reaction/photoinduced double group transfer reaction. Multiple photochemical domino reactions remain undeveloped [43][44][45] because domino reactions initiated by photoirradiation conventionally consist of consecutive thermal steps after the first photochemical step. One advantage of a photochemical domino process over a thermal one is that the domino process can be suspended and restarted at will simply by controlling the irradiation time.…”
Section: Discussionmentioning
confidence: 99%
“…Using F 4 -stilbene 1, we performed a photoinduced domino reaction consisting of three photochemical steps: oxidative photocyclisation/photoinduced Diels-Alder reaction/photoinduced double group transfer reaction. Multiple photochemical domino reactions remain undeveloped [43][44][45] because domino reactions initiated by photoirradiation conventionally consist of consecutive thermal steps after the first photochemical step. One advantage of a photochemical domino process over a thermal one is that the domino process can be suspended and restarted at will simply by controlling the irradiation time.…”
Section: Discussionmentioning
confidence: 99%
“…It represents the first example of the 2-azahexacyclo[8.7.1.11,4.04,9.011,16.012,18] nonadeca-4,6,8-triene skeleton [18,19]. It represents the first example of the 2-azahexacyclo[8.7.1.11,4.04,9.011,16.012,18] nonadeca-4,6,8-triene skeleton [18,19].…”
Section: 9)mentioning
confidence: 99%
“…It represents the first example of the 2-azahexacyclo[8.7.1.11,4.04,9.011,16.012,18] nonadeca-4,6,8-triene skeleton [18,19]. Photochemical transformation of 29 into 30 does not take place in nonpolar solvents such as cyclohexane and occurs very inefficiently in MeCN ( 10-4) [19]. Photochemical transformation of 29 into 30 does not take place in nonpolar solvents such as cyclohexane and occurs very inefficiently in MeCN ( 10-4) [19].…”
Section: 9)mentioning
confidence: 99%
“…In continuation of our interest in the Majerski's laboratory in the functionalization and transformation of cage molecules [3848] as well as the preparation of biologically active compounds [49], we turned our attention to adamantylphthalimides [5052]. Recently, in cooperation with the group of Griesbeck we discovered a photoinduced domino reaction of adamantylphthalimide that involves two consecutive γ H-abstractions and leads to a complex methanoadamantane benzazepinone 2 (Scheme 1) [51].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in cooperation with the group of Griesbeck we discovered a photoinduced domino reaction of adamantylphthalimide that involves two consecutive γ H-abstractions and leads to a complex methanoadamantane benzazepinone 2 (Scheme 1) [51]. The mechanism of the photoinduced domino reaction was investigated and it was found that it probably takes place from a higher excited triplet state or the singlet state [52]. Herein, we report the synthesis and photochemistry of a phthalimide derivative of homoadamantane 5 .…”
Section: Introductionmentioning
confidence: 99%